A novel wide scale well-baby clinic mobile application: an Egyptian pilot study - Noha M. Ibrahim; Hanan S. Ez-Elarab; Mohamed Momen; Isis M. Mossad; Sherif S. Eletriby (BMC, 2023)
Abstract Background Utilization of under 5-year-old child healthcare services in Egypt is considered low, the highest proportion of well-baby visits is mainly for immunization in the first 2 years of age. Mobile health (mHealth) interventions have the potential to be a useful and low-cost way to disseminate information about proper nutrition, can be used to monitor children's growth using the official charts of World Health Organization, can also help in accessing vaccine-related information and schedules. Objectives To assess needs and requirements for a new comprehensive well-baby clinic mobile application (app) covering well-baby clinic service components. Thereafter, to develop the app prototype and validate it. Methods This study was conducted in four phases: User requirements, development, validation and usage. In user requirement phase, the need for the new app was assessed by performing literature review, market app research and an online survey. In development phase, we developed the novel well-baby clinic app that constituted all well-baby clinic services for children's health monitoring relying on evidence-based information and honoring data safety. In validation phase, after a series of testing, the app was validated using Mobile app rating scale (MARS) by public health and pediatrics consultants to assess its quality. Finally, the app was launched and made available to the public on Android platform. Results Sehhat Tefly app was developed based on the demands and requirements of mothers of under 5-year-old children. The app constituted caregiver, child information and seven service elements: physical growth, developmental milestones, immunizations, nutrition, teething, safety & emergency measures and report. The app quality mean was rated 3.7 out of 5 by the panel of experts. The app was downloaded 1445 times in a 4 month period. Conclusions Sehhat Tefly app can meet the need for a free, easy and accessible tool for caregivers to track the progress of children's development and wellbeing. It can also provide advice for referral to physician consultation in case of deviation from normal measures.